Association Between Migraine and Atopic Diseases in Childhood: A Potential Protective Role of Anti‐Allergic Drugs. Issue 4 (4th February 2017) - Aupiais, Camille; Wanin, Stephanie; Romanello, Silvia; Spiri, Daniele; Moretti, Raffaella; Boizeau, Priscilla; Massano, Davide; Zuccotti, Gian Vincenzo; Crichiutti, Giovanni; Kanagarajah, Lakshmi; Houdouin, Veronique; Alberti, Corinne; et al.
Abstract : Background: Migraine is a common cause of headache in childhood. Several studies have investigated the association between migraine and atopic diseases, mostly in the adult population. Objective: This study aimed to investigate this association in children. Methods: A case‐control study was conducted across 3 European tertiary care hospitals between June 2014 and August 2014. Cases (n = 229) were children aged 6‐18 years consulting for a migraine episode. Controls in the same age range (n = 406) were consulting for a minor injury and did not have a history of recurrent headache. Logistic regression analyses tested the effect of atopic diseases and anti‐allergic therapies on occurrence of migraine. Results: Children with migraine were more likely to have persistent asthma compared to absence of asthma (odds ratio [OR]: 4.57, 95% confidence interval [CI]: 2.04‐10.24) and less likely to have been treated by inhaled or nasal corticosteroid (OR: 0.34, 95% CI: 0.15‐0.76) or antihistamine therapy (OR: 0.33, 95% CI: 0.18‐0.60). The median number of monthly migraine episodes was higher in children with persistent asthma (3; interquartile [IQR]: 1‐4; range: 0.5‐10) compared to children with intermittent asthma (2; IQR: 1‐3; range: 0.1‐4) or non‐asthmatic children (2; IQR: 1‐3; range: 0.1‐12) ( P  < .01). Conclusion: Persistent childhood asthma was associated with increased risk of migraine and higher frequency of migraine attacks. History of anti‐asthmatic or anti‐allergic therapies was associated with decreased risk of migraine in children and adolescents. The role of these therapies on the pathogenesis and occurrence of migraine needs to be further elucidated because of the huge potential impact in terms of public health.